Pengaruh Pengenalan Lapangan Persekolahan (PLP) dan Konsep Diri terhadap Minat Menjadi Guru - Luqman, Rafika Mufidha; Dewi, Retno Mustika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to identify the students' attention to become teachers at the 2018 Economics Education Study Program students of the Faculty of Economics, State University of Surabaya with 65 students as respondents. This research is calculated quantitatively using the procedure for collecting information in the form of a questionnaire. The information obtained is processed using SPSS type 25. The results of this study indicate; 1) the variable of School Field Identification has an important influence on the variable of student interest in becoming a teacher (2) the self-design variable has an important influence on the variable of student interest in becoming a teacher (3) and has an important effect together with the variable of School Field Identification and self-scheme on the interest of students to become a teacher . In conclusion, the introduction of the PLP School Field has a positive and important impact on student interest in becoming a teacher at the 2018 Economics Education Study Program students at the State University of Surabaya. Keywords: Self-Concept, Interest in Becoming a Teacher, Introduction to School Field